SYNTHESIS, CHARACTERIZATION AND ANTI-MICROBIAL ACTIVITIES OF NOVEL THIAZOLE DERIVATIVES - G. SARAVANAN; V. ALAGARSAMY; T.G.V. PAVITRA; G. CHANUKYA KUMAR; Y. SAVITHRI; L. NARESH; P. AVINASH (International Journal of Pharma and Bio Sciences, 2010)
Various substituted 3-amino-1-(2,4-dinitro phenyl)-5-[(5-substituted-1,3,4-oxadiazol-2-yl)amino]-1-Hpyrazole-4-carboxyamide and (5E)-5-[4-(dimethylamino) benzylidene]-3-(5-substituted-1,3,4oxadiazol-2-yl)-2-phenyl-3,5-di hydro-4H-imidazol-4-one containing different functional groups have been synthesised by using different aromatic aldehydes and semicarbazide. Different aldehydes and semicarbazide react to form semicarbazone. This was reacted with I2/KI solution to get corresponding 5-substituted-1,3,4-oxadiazol-2-amine. Half of the substituted oxadiazole condensed with Bis-s-methyl ethylene cyanoacetmide and finally with 2,4-dinitro phenyl hydrazine HCl in ethanol gives 3-amino-1-(2,4-dinitro phenyl)-5-[(5-substituted-1,3,4-oxadiazol-2-yl)amino]-1-H-pyrazole-4carboxyamide. Half of the substituted oxadiazole condensed with oxazolone in pyridine gives (5E)-5[4-(dimethylamino) benzylidene]-3-(5-substituted-1,3,4-oxadiazol-2-yl)-2-phenyl-3,5-di hydro-4Himidazol-4-one. The identity of compounds were confirmed on the basis of their spectral data. All the compounds have been screened for their anthelmintic activity.